"[The] immediate heft of bodily and civic catastrophe": the body (politic) in crisis in Mike McCormack's Solar Bones. Issue 3 (3rd July 2021) - Darling, Orlaith
ABSTRACT: Solar Bones encompasses several interlinked crises. Mike McCormack's 2016 Goldsmith Prize-winning novel speaks to the 2008 financial crash, the environmental and health crisis that was the 2007 cryptosporidium outbreak, political crises such as the Eighth Amendment and Citizenship Referendum, as well as various personal crises which link the local and national body politic. Throughout, McCormack is concerned with the engineering and collapse of societal foundations, but also in the ways in which crisis is experienced and embodied. Within the corrupt political system of the novel, the common good – supposedly ensured by failing, patriarchal institutions – is outsourced to women. This is true of a number of contemporary Irish social ruptures, such as the 2004 Citizenship Referendum and the Eighth Amendment which are explored in relation to Solar Bones 's exploration of female embodiment. Crisis in the novel is a gendered, embodied experience, represented both by Mairead's severe illness and Agnes's art. Although Mairead recovers, her body remains a site of (male) political failures. Similarly, Agnes fails to evade woman's role as symbol of nation/community and merely embodies the political machinations outside of her control.